A Community Directed Interventional Approach to Promote Breast Self-Examination Through BEHENA Among Women Residing in Rural Villages of Hingna, Nagpur District - Saurabh R Shrivastava; Prithvi Petkar; Sonali Borkar; Harshal Mendhe; Gulshan Bandre (Medsci Publications, 2024)
Introduction: The practice of breast self-examination (BSE) does not adopt a community-directed approach, and hence lack the influence of community dynamics. Community-directed strategy to promote BSE through Breast Examination Health Education Network Advocator (BEHENA) acknowledges the impact of collective support. Objectives: To increase the knowledge and empower women aged ≥20 years with the help of BEHENA in correctly performing BSE and to identify the perception and challenges encountered by BEHENA in promoting BSE. Methods: A mixed-methods study design will be employed, wherein in the first phase, local women satisfying eligibility criteria will be selected as BEHENA and trained in BSE. In the second phase, these BEHENA workers will sensitize and train the study participants in BSE. In the third phase, the participants will be periodically monitored to monitor BSE sustenance practice. Finally, focus group discussions will be conducted to identify their perceptions and challenges encountered in promoting BSE. Results: An improvement in awareness levels and empowerment of rural women with the skills necessary to perform accurate and effective BSE. Conclusion: Upon the completion of the project, the best practices and lessons learned during the entire duration of implementation will be documented. The findings of the study will be shared with all the concerned stakeholders.